N-Palmitoyl-ethanolamine (PEA) Induces Peripheral Antinociceptive Effect by ATP-Sensitive K+-Channel Activation - Thiago Roberto Lima Romero; Igor Dimitri Gama Duarte (Elsevier, 2012)
Although the antinociceptive effects of N-palmitoyl-ethanolamine (PEA) were first characterized nearly 50 years ago, the identity of the mechanism that mediates these actions has not been elucidated. The present study investigated the contribution of K+ channels on peripheral antinociception induced by the CB2 agonist PEA. Nociceptive thresholds to mechanical paw stimulation of Wistar rats treated with intraplantar prostaglandin E2 to induce hyperalgesia were measured, and other agents were also given by local injection. PEA (5, 10, and 20 μg/paw) elicited a local peripheral antinociceptive effect. This effect was antagonized by glibenclamide, a selective blocker of ATP-sensitive K+ channels (20, 40, and 80 μg/paw). In addition, neither the voltage-dependent K+ channel-specific blocker tetraethylammonium (30 μg/paw) nor the small and large conductance blockers of Ca2+-activated K+ channels, dequalinium (50 μg/paw) and paxilline (20 μg/paw), respectively, were able to block the local antinociceptive effect of PEA. These results indicate that the activation of ATP-sensitive K+ channels could be the mechanism that induces peripheral antinociception by PEA and that voltage-dependent K+ channels and small and large conductance Ca2+-activated K+ channels do not appear to be involved in this mechanism. Keywords:: N-palmitoyl-ethanolamine (PEA), K+ channel, cannabinoid agonist, CB2 agonist, peripheral antinociception